Performance of agricultural tractor consuming diesel and biodiesel derived from babassu (Orbinya martiana) - Lira, Thyago Augusto Medeiros [UNESP] (2019)
Biodiesel is an alternative fuel to diesel engines. This study aimed to evaluate fuel consumption and smoke density of agricultural tractors fueled by biodiesel, diesel, and biodiesel/diesel mixtures in a tilled field. Treatments consisted of distilled methyl ester (biodiesel) of babassu (Orbinya martiana) and seven combinations of it with two standard diesel fuels (B S1800 and B S50). The blending ratios were 0, 5, 15, 25, 50, and 100% biodiesel in diesel oil (B0, B5, B15, B25, B50, and B100, respectively). Regarding the results for hourly volumetric consumption, no difference was found between B0 and B100 when using B S1800, whereas an 8% increase was observed when using the S50. The weighted hourly consumption increased by 11.29 and 16.9% from B0 to B100 using B S1800 and B S50, respectively. Similarly, the specific fuel consumption increased by 11.1% and 14.3% from B0 to B100 using B S1800 and B S50, respectively. Yet, when comparing B0 and B S1800, the smoke density reduction was 68.6% and between B S50 and B100 was 58.0%. Our findings show that babassu biodiesel is a suitable substitute for diesel oil, without causing any damage to the tractor's engine.